2013
DOI: 10.1016/j.jcyt.2013.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Cell-based approaches to the engineering of vascularized bone tissue

Abstract: This review summarizes recent efforts to create vascularized bone tissue in vitro and in vivo using cell-based therapy approaches. The treatment of large and recalcitrant bone wounds is a serious clinical problem, and in the United States approximately 10% of all fractures are complicated by delayed or non-union. Treatment approaches using growth factor and gene delivery have shown some promise, but results are variable and clinical complications have arisen. Cell-based therapies offer the potential to recapit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 124 publications
1
58
0
1
Order By: Relevance
“…This is an important physiological aspect since bone is a highly metabolic tissue requiring an abundant vascular supply throughout its structure for growth, remodeling, and repair abilities [52]. Our results about the improvement of bone repair and angiogenesis obtained with the implantation of MSCs are consistent with numerous previously published studies [53].…”
Section: Discussionsupporting
confidence: 91%
“…This is an important physiological aspect since bone is a highly metabolic tissue requiring an abundant vascular supply throughout its structure for growth, remodeling, and repair abilities [52]. Our results about the improvement of bone repair and angiogenesis obtained with the implantation of MSCs are consistent with numerous previously published studies [53].…”
Section: Discussionsupporting
confidence: 91%
“…Genetically-modified MSCs can be cultured to produce varying combinations of growth factors such as bFGF and VEGF, BMP-2 and BMP-7, and VEGF and BMP-4. (18) Before implantation at the defect site, gene transfer to these cells can be performed ex vivo using viral vectors and then combined with polymers, such as collagen type I, to create cell/polymer constructs. (19) Various studies have also reported the use of ex vivo expanded autologous bone marrow-derived osteoprogenitor cells grown on macroporous hydroxyapatite scaffolds for implantation at lesion sites.…”
Section: Tissue Engineering Strategies To Regenerate Bonementioning
confidence: 99%
“…Bioreactors provide an artificial proxy for vascularization via continuous in-flux of nutrients and oxygen and out-flux of waste materials through the bioreactor system [1217]. On the other hand, co-culture with endothelial cells (e.g., model cell types such as HUVECs or endothelial progenitor cells [EPCs]), establishes natural vascularization within the scaffold via the formation of blood vessels [18, 19]. …”
Section: Introductionmentioning
confidence: 99%